2021
DOI: 10.1177/25165984211021010
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous improvement of microgeometry and surface quality of spur and straight bevel gears by abrasive flow finishing process

Abstract: This article reports on influence of extrusion pressure, abrasive particle size and volumetric concentration on simultaneous reduction of surface roughness and microgeometry errors of spur and straight bevel gear by abrasive flow finishing (AFF) process. A vertical configured experimental apparatus was developed for two-way AFF and developed fixtures for finishing gears. Experimental investigations were conducted to identify optimum parametric combination, using response surface methodology, based on Box–Behnk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…A schematic illustration of atomic diffusion additively manufactured copper before and after surface finishing in the mentioned medium is presented in Figure 7. An opposite effect of the particle size was observed in the work by Petare et al [64]. They showed that increasing abrasive particle size can decrease the surface roughness of spur and straight bevel gears.…”
Section: Abrasive Flow Finishing (Aff)mentioning
confidence: 82%
“…A schematic illustration of atomic diffusion additively manufactured copper before and after surface finishing in the mentioned medium is presented in Figure 7. An opposite effect of the particle size was observed in the work by Petare et al [64]. They showed that increasing abrasive particle size can decrease the surface roughness of spur and straight bevel gears.…”
Section: Abrasive Flow Finishing (Aff)mentioning
confidence: 82%